Postgenocide : interdisciplinary reflections on the effects of genocide - Mulaj, Klejda (Oxford : Oxford University Press, 2021)
This edited volume studies the after-effects of genocide, exploring the ways in which societies are shaped by a history of such extreme violence. Contributions from a variety of perspectives, including law, political science, sociology, and ethnography, explore previously overlooked themes and cases to reassess existing assumptions in the field.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 15, 2021).
Keywords: Genocide; Reconciliation; Transitional justice